Monotheism and christology in I Corinthians 8. 4-6 - Rainbow, P (1987)
The thesis is a description of the relationship between the 'one God, the Father' and the 'one Lord, Jesus Christ' in I Cor. 8. 4-6. It analyses Paul's language about God and Christ against the background of contemporary Jewish language about the one God, making use of methodic concepts gleaned eclectically from the structural movement in linguistics and the social sciences. Accordingly, the study falls into two parts: a determination of Paul's Jewish monotheistic presuppositions, and an analysis of I Cor. 8. 4-6 itself. Part one uses the Greek Old Testament, the Apocrypha, the Pseudepigrapha, the Dead Sea Scrolls, Philo, Josephus, and the New Testament, in particular some two hundred statements of monotheism collected from these sources (presented in an appendix), to illuminate the oblique references to monotheistic belief in Paul's letters. This part of the study concentrates on answering a series of nine questions about Jewish monotheism designed to shed light on Paul's language in our chosen passage. Part two combines the familiar grammatical-historical methods of biblical scholarship with newer, structural methods of exegesis to investigate the doctrinal content of the quasi-confessional language about God and Christ in I Cor. 8 4-6 in the light of our results from part one. The major conclusions of the study can be summarized in three statements. (1) I Cor. 8. 6 contains two classic statements of monotheism using traditional Jewish language, one in reference to the Father and one in reference to Jesus Christ; in each case, the language of monotheism comprehends not only the explicit confession with 'one', but also the prepositional phrases, which contain elements closely associated with belief in one God in Jewish thought. (2) Paul's paradoxical language about God and Christ in this passage certainly expresses the functional subordination of Christ to God, but it very probably presupposes an identity of these two figures at some undefined point, an identity which may well be essential in nature (by comparison especially with Gal. 4.8). (3) The language about Christ in I Cor. 8. 6. is informed not so much by Jewish Wisdom speculation as by Jewish language about the one God: it is best labelled a 'monotheism christology'. Hence the contribution of the thesis to knowledge lies in three areas. (1) It clarifies the nature and associations of Jewish monotheistic language. (2) It provides scientific support for the view, by no means generally accepted, that the New Testament adumbrates the concept of the ontological deity of Christ, using the most current methods of exegesis and working with a comprehensive selection of comparative Jewish materials. (3) It brings to the fore a christological category - the language of monotheism - which has been largely overlooked by researchers in the field of the origins and development of christology in the early church.